Sistem Jual Beli Online dalam Perspektif Hukum Islam: Studi Kasus di Facebook Temanggung - Isnaeni; Ida Nurlaeli (Masyarakat Ekonomi Syariah Bogor, 2024)
This reseach contains at study of online buying and selling systems in the perspective of islamic law in tehe buying and selling process of online facebook grups for wong temanggung. This research uses deskriptive qualitative research menthods. The results of this study found that there was a sale and purchase that me the requirements and harmony, but someting the seller and buyer met in a virtual assembly because sellers and buyers are not in one country sometimes meet face to face for affordability place according to the rules written on facebook.